Basic Properties of Ganitri Wood (Elaeocarpus sphaericus (Gaertn.) K. Schum.) from Sukabumi and Its Potential Uses - Esti Prihatini; Akhrudin Maddu; Istie Sekartinging Rahayu; Mersi Kurniati (Jurnal Ilmu Kehutanan)
Ganitri (Elaeocarpus sphaericus (Gaertn.) K. Schum.) is a fastgrowing tree that is widely found in Sukabumi, West Java. It grows in all part of Indonesia. A research was carried out to investigate basic properties (anatomical, physical, mechanical, and chemical) of ganitri wood from the community forest of Sukabumi. The purpose of this study was to determine the potential use of ganitri wood based on its basic properties and local utilization. The results showed that the color of ganitri sapwood was white , and it was not clearly demarcated from the yellow, with fewer figure patterns. The texture was fine with straight to interlocked grain. The wood was soft, not lustrous, and no special odor. Based on the fibre dimensions and derivative values, the quality of ganitri wood fell in Class II as a raw material for pulp and paper. Ganitri had high holocellulose and cellulose levels (70.70% and 54.58%), moderate level in lignin (21.60%), and it contained 3.47% extractive soluble in alcohol-benzene, and 0.81% ash. Based on its air dry specific gravity (0,35), ganitri wood could be classified into wood Strength Class IV. The potential uses of ganitri are for lightweight construction material, tools, furniture, plywood, connecting boards, and other panel products.